Metabolic syndrome, its components, and gastrointestinal cancer risk: a meta‐analysis of 31 prospective cohorts and Mendelian randomization study - Zhan, Zhi‐Qing; Chen, Ying‐Zhou; Huang, Ze‐Min; Luo, Yu‐Hua; Zeng, Jia‐Jian; Wang, Ye; Tan, Juan; Chen, Ying‐Xuan; Fang, Jing‐Yuan (Journal of gastroenterology and hepatology, 2024)
Background and Aim Cohort studies have linked metabolic syndrome (MetS) to gastrointestinal (GI) cancer risk. We aimed to evaluate the associations between MetS, its components, and combinations of MetS components with eight GI cancers risk. Methods We conducted a systematic search of prospective cohort studies and performed a meta‐analysis. Subgroup analyses regarding diagnostic criteria, sex, cancer sites, histological subtypes, ethnic groups, and studies adjusted for alcohol consumption were carried out. Mendelian randomization (MR) was employed to evaluate the causality between 17 MetS‐related traits and eight GI cancers among Europeans and Asians separately. Results Meta‐analyses of 31 prospective studies indicated that MetS was significantly associated with an increased risk of colorectal cancer (CRC) (RR [95% CI] = 1.13 [1.12–1.15]), esophageal cancer (EC) (RR [95% CI] = 1.17 [1.03–1.32]), gallbladder cancer (GBC) (RR [95% CI] = 1.37[1.10–1.71]), liver cancer (LC) (RR [95% CI] = 1.46 [1.29–1.64]), and pancreatic cancer (PaC) (RR [95% CI] = 1.25 [1.20–1.30]), but not gastric cancer (GC) (RR [95% CI] = 1.11 [0.96–1.28]). Regarding the associations between MetS components and GI cancers risk, the following associations showed statistical significance: obesity‐CRC/LC/EC/, hypertriglyceridemia‐LC/PaC, reduced high‐density lipoprotein (HDL)‐CRC/LC/GC/PaC, hyperglycemia‐CRC/LC/PaC, and hypertension‐CRC/LC/EC/PaC. Sex‐specific associations were observed between individual MetS components on GI cancers risk. Among the top three common combinations in both sexes, obesity + HTN + hyperglycemia had the strongest association with CRC risk (RR [95% CI] = 1.54 [1.49–1.61] for males and 1.27 [1.21–1.33] for females). MR analyses revealed causality in 16 exposure–outcome pairs: waist‐to‐hip ratio/BMI/HbA1c‐CRC; BMI/childhood obesity/waist circumference/T2DM/glucose‐EC; BMI/waist circumference/cholesterol‐LC; cholesterol/childhood obesity/waist circumference/HbA1c‐PaC; and HbA1c‐GBC. These results were robust against sensitivity analyses. Conclusions Since MetS is reversible, lifestyle changes or medical interventions targeting MetS patients might be potential prevention strategies for GI cancers.